Combinatorial optimization of resilience engineering and organizational factors in a gas refinery by a unique mathematical programming approach. Issue 1 (9th November 2016) - Azadeh, A.; Salehi, V.; Mirzayi, M.; Roudi, E.
Abstract: This study is an attempt to evaluate the mutual impacts of resilience engineering (RE) and managerial and organizational factors in a large gas refinery. RE is a paradigm for safety management that focuses on how to help people cope with complexity under pressure to achieve success. The data obtained from questionnaire are analyzed by statistical methods and data envelopment analysis (DEA) approach. The results of Cronbach's alpha test show that the data are reliable. The results of DEA demonstrate that learning and flexibility among all RE factors have the greatest impact on managerial and organizational factors. In addition, the organizational factors have a greater influence on RE in comparison with managerial factors. Spearman's test was used to verify the results of this study. This is the first study that identifies the most important factors of integrated managerial and organizational factors and RE through a unique mathematical programming approach in a gas refinery.